(untitled) (KYAMC Journal, 2023)
Several treatment options may help improve daily functioning in children with cerebral palsy (CP). However, these treatments cannot prevent early death or enable them to lead independent life without support. CP is a progressive disease, and even in its milder form, conditions such as Parkinson’s disease, epilepsy, and stroke may develop even after 25 years. A new era of curable treatment has emerged for CP, utilizing bilateral cranioplasty and duraplasty (Tanfarid Procedure). This case report describes a successful case where this procedure was employed. During the surgery, after the removal of cranial bones through craniotomy, the absence of dural pulsation was observed, indicating elevated intracranial pressure. After duraplasty, normal brain pulsation was observed, indicating that intracranial pressure had normalized. In patients with CP, premature closure of sutures and thickening of skull bones lead to a reduced intracranial volume, which hinders proper brain growth and eventually results in brain atrophy, widened Sylvian issures, and widened sulci accompanied by the loss of brain parenchymal tissue. These findings were also evident in the patient’s brain CT scan. In this case, cranioplasty and duraplasty provided adequate space for the brain to grow . The treatment of CP patients typically involves a multidisciplinary approach, which can be expensive. However, the procedure utilized in this case is affordable for economically disadvantaged individuals in this country. While a second cranial surgery may be required in some cases, the expenses associated with it are significantly lower compared to a lifetime of physiotherapy and other supportive treatments. Additionally, the outcomes are very promising. KYAMC Journal Vol. 14, No. 02, July 2023: 105-108.